Human Resource Management Practices in the Nepalese Hospitality Industry: A Case from Chitwan - Sapkota, Shiva Prasad; Neupane, Pradeep (Nepalese Journal of Hospitality and Tourism Management, 2025)
This study examines human resource management (HRM) practices in Nepal’s hospitality industry, focusing on selection/recruitment, training and development, information technology (IT) usage, and human capital. Using a descriptive and correlational design, data were collected from 101 employees in Chitwan-based hotels. Findings indicate positive perceptions of recruitment processes, emphasising candidate potential and teamwork, though interpersonal skills were undervalued. Training initiatives were well regarded, but training hours lagged industry standards. IT systems were seen as integrated but needed improvements in accessibility and updates. Human capital was highly rated for expertise but scored lower in innovation. Correlation analysis revealed strong links between effective recruitment, training, IT use, and human capital quality. The study underscores the need for refined HRM strategies to enhance workforce competency and organisational performance in Nepal’s growing hospitality sector.